FDI and growth: a causal relationship - Abdur Chowdhury; George Mavrotas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
The paper examines the causal relationship between FDI and economic growth by using an innovative econometric methodology to study the direction of causality between the two variables. We apply our methodology, based on the Toda-Yamamoto test for causality, to time-series data covering the period 1969-2000 for three developing countries, namely Chile, Malaysia and Thailand, all of them major recipients of FDI with a different history of macroeconomic episodes, policy regimes and growth patterns. Our empirical findings clearly suggest that it is GDP that causes FDI in the case of Chile and not vice versa, while for both Malaysia and Thailand, there is a strong evidence of a bi-directional causality between the two variables. The robustness of the above findings is confirmed by the use of a bootstrap test employed to test the validity of our results. – FDI ; economic growth ; causality ; Toda-Yamamoto test
Keywords: F39; O4; C32; 330; Direktinvestition; Wirtschaftswachstum; Kausalanalyse; Zeitreihenanalyse; Entwicklungsländer; Chile; Malaysia; Thailand